RANCANG BANGUN SISTEM INFORMASI PENGINGAT JADWAL PEMBAYARAN ANGSURAN PADA KOSPIN JASA CABANG PEMALANG BERBASIS SMS GATEWAY (Information Technology and Telematics, 2013)
SMS (Short Message Service) has been used by humans. Besides having a wide range, to reach rural areas, easy to use and efficient SMS, SMS Gateway is a two-way communication using the normal rates in accordance with the rates applied by the operator. SMS Gateway has a variety of types. In Kospin Jasa Branch Pemalang has built reminder application client loan repayment schedule based on SMS. In this application, the authors utilize SMS Gateway application with two features, namely SMS Reminder (Reminder) and SMS Autorespon. With the SMS Reminders, is expected to assist customers in reminding the loan repayment schedule, while via SMS Autorespon customers can check the loan repayment schedule. The programming language used in designing the SMS application is PHP. For data storage, the authors use MySQL. As for building SMS applications, the authors use Gammu. This application can remind clients installment payment schedule four times, ie on the day before the due date which is seven days and three days before the due date, on the day or right on the due date, and on the day after the installment due date loan customer.  Keywords: SMS (Short Message Service), Gammu, SMS Gateway, SMS Reminder, SMS Autorespon.